A solder bridging rework study and an experimental investigation of the TuMR magnetic head - Reangroaj Roajanasiri; Nitin Afzulpurkar; Siridech Boonsang (My University, 2012)
The TuMR reader was designed with high sensitivity for high areal density magnetic recording in the hard disk drive. The assembly process requires the use of solder jet welding on small connectors in the head circuit. The solder bridging problem is the cause of the major mechanical yield loss. This work considers how to resolve the bridging problem without degrading the TuMR sensor by examining the use of Nd:YAG laser reheating. The use of double laser pulses yields better results than the use of single pulses. The critical parameters of the TuMR sensor are monitored with the Quasi tester.
Keywords: Adhesion, Friction, and Surface Interactions